Maritime terminology in the Lexicon, or Vocabulario de la lengua general del Perú by Domingo de Santo Tomás (1560) and possible implications for the history of the Quechua language family - Urban, Matthias (2021)
Although the author of the first grammatical and lexicographical documentation of Quechua, Domingo de Santo Tomás, does not mention anywhere in his extensive works the dialectal and geographical basis of his work, it is commonly assumed that it is an extinct Quechua dialect of the central coast of Peru. In this paper, I review the arguments supporting this dialectal identification and discuss some problematic aspects that are known but worth emphasizing. In this context, I offer an exhaustive discussion of the Lexicon, or Vocabulario de la lengua general del Perú by Santo Tomás, specifically the vocabulary related to the sea. Based on the extensive documentation of expressions belonging to the maritime semantic field (references to the sea, marine life, fish, fishing, navigation) found in the Lexicon, or Vocabulario de la lengua general del Perú, we can conclude that the Quechua described by Santo Tomás had lexically been adapted to a coastal environment. The properties of the relevant expressions, which often seem to be semantic adaptations of inherited Quechua words to this domain, or neologisms, or loanwords from other coastal languages, suggest, however, that a significant percentage of the vocabulary was added relatively later to the lexical stock. In turn, this observation is evidence that would support the idea that the coastal dialect originated away from the coast. The relevance of this observation is discussed in relation to theories that place the origin of the Quechua language family in the central coast, which would lead us to expect a maritime vocabulary with deeper roots in the lexicon.